2007
DOI: 10.1039/b615118c
|View full text |Cite
|
Sign up to set email alerts
|

Air pollutants and the characterization of the organic content of aerosol particles in a mixed industrial/semi-rural area in central Italy

Abstract: Both regulated and unregulated air pollutants were detected during an intensive seasonal sampling campaign in a mixed industrial/semi-rural area on the outskirts of Rome, Italy, at two sites located opposite a hospital waste incinerator, downwind according to the direction of the prevailing local winds. Concentrations of pollutants were significantly lower than in urban atmospheres. The composition of particulate organic material indicated a heavy biogenic impact, accompanied by a lower contribution from petro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…It is important to note that PAH concentrations used in this study were largely (at least one order of magnitude) below those used by other Investigators. Indeed, the levels used here were chosen based upon concentrations of the PAHs commonly found in PM (Baulig et al, 2004;Di Filippo et al, 2007). Under these conditions, it was shown here that B[a]P was able to induce secretion of IL-1β, IL-8, and IL-12, with or without LPS stimulation; the only exception to this stimulatory outcome was with IL-10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that PAH concentrations used in this study were largely (at least one order of magnitude) below those used by other Investigators. Indeed, the levels used here were chosen based upon concentrations of the PAHs commonly found in PM (Baulig et al, 2004;Di Filippo et al, 2007). Under these conditions, it was shown here that B[a]P was able to induce secretion of IL-1β, IL-8, and IL-12, with or without LPS stimulation; the only exception to this stimulatory outcome was with IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…of DEP (SRM 2975) and urban dust (SRM 1649a) revealed that apart from benzo [a]pyrene (B[a]P), benzo [b]fluoranthene (B[b]F) and pyrene (Pyr) are also quantitatively important; each of these PAH has also been detected on PM 2.5 in several European cities (Baulig et al, 2004;Di Filippo et al, 2007). As such, B[a]P, B[b]F and Pyr could significantly contribute to the toxic effects of air pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Silica cartridges [22,27], alumina cartridges [27] or HPLC [14] have always been used during the clean-up procedure. Although there have been some research focusing on the determination of SPAHs in air and soil samples, especially a single type of SPAHs, such as NPAHs [29,30] or OPAHs [31], and a recent study solely focusing on the determination of NPAHs in aqueous samples [32], the analytical methods of SPAHs in the natural water environment have not been well documented. Moreover, the existing methods used in air and soil samples are rather complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Nitro-and oxoaromatic compounds are by far the best-studied mutagenic components of SOA (e.g. Enya et al, 1997;Di Filippo et al, 2007;Huang et al, 2014). They can form upon the oxidation of primary organic compounds which can be also mutagenic (PAHs) or that are just non-toxic, such as methoxy-phenols in biomass burning emissions (Kroflič et al, 2015).…”
Section: Cluster Analysismentioning
confidence: 99%